Characterisation of freeze-dried flaxseed oil microcapsules obtained by multilayer emulsions - Fioramonti, Silvana Alejandra (2017)
The aim of this study was to obtain and characterise freeze-dried flaxseed oil microcapsules containing variable maltodextrin concentrations and to evaluate the influence of microencapsulation processing steps on the oxidative stability of the oil. Multilayer emulsions were obtained by performing sodium alginate electrostatic deposition onto whey protein isolate coated oil droplets at pH 5. Maltodextrin was also added in different concentrations (0–20 wt%), and the systems were then freeze-dried. Powdered microcapsules were characterised through scanning electron microscopy, encapsulation efficiency and water activity determinations. Oxidative stability of flaxseed oil was also examined by measuring peroxide values and thiobarbituric reactive substances to evaluate primary and secondary oxidation, respectively, at different processing steps. Encapsulation efficiency above 90% was reported in powders containing the highest maltodextrin concentration. Water activity of freeze-dried microcapsules ranged between 0.14 and 0.33, and increased when increasing maltodextrin concentration. However, ultrasonic emulsification and freeze-drying process seemed to have contributed significantly to oxidation of the oil, thus affecting powdered microcapsules oxidative stability. These results could contribute to expand scientific knowledge to improve designing of functional ingredients.